Ligand-Receptor Interactions of Galectin-9 and VISTA Suppress Human T Lymphocyte Cytotoxic Activity - Yasinska, Inna M.; Meyer, N. Helge; Schlichtner, Stephanie; Hussain, Rohanah; Siligardi, Giuliano; Casely-Hayford, Maxwell; Fiedler, Walter; Wellbrock, Jasmin; Desmet, Cloe; Calzolai, Luigi; Varani, Luca; Berger, Steffen M.; et al. (Frontiers in Immunology, 2020)
Acute myeloid leukaemia (AML), a blood/bone marrow cancer, is a severe and often fatal malignancy. AML cells are capable of impairing the anti-cancer activities of cytotoxic lymphoid cells. This includes the inactivation of natural killer (NK) cells and killing of T lymphocytes. Here we report for the first time that V-domain Ig-containing suppressor of T cell activation (VISTA), a protein expressed by T cells, recognises galectin-9 secreted by AML cells as a ligand. Importantly, we found that soluble VISTA released by AML cells significantly enhances the effect of galectin-9 most likely by forming multiprotein complexes on the surface of T cells and possibly creating a molecular barrier. These events cause changes in the plasma membrane potential of T cells leading to activation of granzyme B inside cytotoxic T cells, which results in their programmed death.